O pewnym „kazachskim” petroglifie i jego „podróży” w czasie i przestrzeni. Refleksja o społecznej adaptacji przeszłości - Rozwadowski, Andrzej (My University, 2014)
Author of the paper discusses social implications of the choice of a prehistoric rock art image as a graphic symbol of the Institute of Ethnology and Cultural Anthropology of the Adam Mickiewicz University. The essay is divided into two parts. The first one deals with implications which result from using a petroglyph as a rock art image. In this matter the paper stresses interpretative context of reading this petroglyph in terms of otherness, both on formal and epistemological levels. In the second part the author considers implications which result from choosing this particular petroglyph, which comes from Kazakhstan. Author demonstrates different social involvements of such a choice, which however well define a nature of cultural anthropology as an academic discipline, which, by definition, faces numerous epistemological and ethical dilemmas in its practice.
About a “Kazakh” petroglyph and its “journey” in time and space. Reflection on social adaptation of the past
Keywords: sztuka naskalna; Kazachstan; Azja Środkowa; Central Asia; tożsamość; identity; adaptacja przeszłości